PERUBAHAN MODUL PEMBERITAHUAN IMPOR BARANG VERSI 5.0.7 MENJADI 6.0.5 DALAM MENINGKATKAN ARUS DOKUMEN IMPOR UDARA - Rr. Endang Wahyuni Andri; Maulana Qopi Azary; Suprihadi Suprihadi (Institut Transportasi dan Logistik Trisakti, 2018)
The purpose of the study was to find out the result of the module changes itself and the effect of the changes. The problem of the study was to find out the changes of PIB module in logistics companies in Indonesia from 5.07 to 6.0.5 version. To solve the problem, the researchers were using the Comparative Descriptive method. The result of the study shows that there are not many changes from the old to the new version. Instead of new additional column and need highly thorough and detailed information of the products identity in those additional new columns, the way to fill those forms are still the same.